Transformations and Remembrances in the Digital Game We Sing for Healing - LaPensee, Elizabeth A. (Transmotion, 2017)
Digital games, with their capacity for expression and facilitating experience through code, design, art, and audio, offer spaces for Indigenous creatives to contribute to Gerald Vizenor’s characterization of survivance as an active sense of Native presence. Indigenous digital games can be acts of survivance both in the ways they are created as well as the resulting designs. We Sing for Healing is an experiment in developing an Indigenous digital game during limited Internet access that resulted in a musical choose-your-own adventure text game with design, art, and code by Anishinaabe, Métis, and Irish game developer Elizabeth LaPensée alongside music by Peguis First Nation mix artist Exquisite Ghost. The non-linear gameplay expresses traditional storytelling patterns while enabling players to poetically travel in, through, and around traditional teachings. The design uses listening, choosing, and revisiting to reinforce what is best described as a non-linear loopular journey.
Number: 1
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Honour water: Gameplay as a Pathway to Anishinaabeg Water Teachings - LaPensée, Elizabeth (Decolonization: Indigeneity, Education & Society, 2018)
Digital games can uniquely express Indigenous teachings by merging design, code, art, and sound. Inspired by Anishinaabe grandmothers leading ceremonial walks known as Nibi Walks, Honour Water (http://www.honourwater.com/) is a singing game that aims to bring awareness to threats to the waters and offer pathways to healing through song. The game was developed with game company Pinnguaq and welcomes people from all over to sing with good intentions for the waters. The hope is to pass on songs through gameplay that encourages comfort with singing and learning Anishinaabemowin. Songs were gifted by Sharon M. Day and the Oshkii Giizhik Singers. Sharon M. Day, who is Bois Forte Band of Ojibwe and one of the founders of the Indigenous Peoples Task Force, has been a leading voice using singing to revitalize the waters. The Oshkii Giizhik Singers, a community of Anishinaabekwe who gather at Fond du Lac reservation, contribute to the healing for singers, communities, and the waters. Water teachings are infused in art and writing by Anishinaabe and Métis game designer, artist, and writer Elizabeth LaPensée. From development to distribution, Honour Water draws on Indigenous ways of knowing to reinforce Anishinaabeg teachings with hope for healing the water.
Number: 1
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

“I see my ancestors”: Exploring Tribal College Student Experiences Playing When Rivers Were Trails - Emmons, Nichlas; LaPensee, Elizabeth (AlterNative: An International Journal of Indigenous Peoples, 2021)
The educational video game, When Rivers Were Trails, was launched in 2019. The purpose of the game is to teach players about Indigenous perspectives of history, US federal allotment policies affecting tribal nations, and some of the effects of these policies on Indigenous peoples. This article explores tribal college student experiences playing When Rivers Were Trails in hopes that it provides the basis for further research into how tribal college faculty may be able to teach the game within their own classrooms. Tribal colleges and universities were created by tribal nations to provide for the higher education needs of their citizens. Using phenomenological research methods, seven college students volunteered to participate in a brief study about their experiences playing the video game. Upon transcription and analysis of the interview data, three themes were developed that capture how these students define their experience with When Rivers Were Trails: feelings of representation, histories of land dispossession, and resilience of communities.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Towards Sovereign Games - LaPensée, Elizabeth A.; Laiti, Outi; Longboat, Maize (Games and Culture, 2021)
Video games can be dynamic sovereign spaces for Indigenous representation and expression when the self-determination of Indigenous people is supported. Where ga...
Publisher: SAGE PublicationsSage CA: Los Angeles, CA
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Learning, Education & Games, Volume 3: 100 Games to Use in the Classroom & Beyond - Schrier, Karen (ETC Press, 2019)
Have you ever wanted to know which games to use in your classroom, library, or afterschool program, or even at home? Which games can help teach preschoolers, K-12, college students, or adults? What can you use for science, literature, or critical thinking skills? This book explores 100 different games and how educators have used the games to teach - what worked and didn't work and their tips and techniques. The list of 100 goes from A to Z Safari to Zoombinis, and includes popular games like Fortnite, Call of Duty: Modern Warfare, and Minecraft, as well as PC, mobile, VR, AR, card and board games.
Google-Books-ID: D_HCDwAAQBAJ
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Thunderbird Strike: Survivance in/of an Indie Indigenous Game - LaPensée, Elizabeth (Video Game Art Reader 2.1, 2018)
Thunderbird Strike, a 2D side-scroller developed by Elizabeth LaPensée, allows a player fly from the Tar Sands to the Great Lakes as a thunderbird protecting Turtle Island with searing lightning against the snake that threatens to swallow the lands and waters whole. The game encouraged players to learn about the indigenous culture, reflect on water protection and alternative energy sources, and gain awareness of risks posed by oil pipeline construction for the conveyance of tar sands.Thunderbird Strike was developed through residencies including O k’inādās Residency, The Banff Musicians in Residence Program, and Territ-Aur(i)al Imprints Exchange thanks to the 2016 Artist Fellowship grant from the Arrowhead Regional Arts Council.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

When Rivers Were Trails: Cultural Expression in an Indigenous Video Game - LaPensée, Elizabeth (International Journal of Heritage Studies, 2021)
When Rivers Were Trails is a 2D adventure game wherein The Oregon Trail meets Where the Water Tastes Like Wine through an Indigenous lens. The game depicts a myriad of cultures during the player’s journey from Minnesota to California amidst the impact of land allotment in the 1890s. Initiated by the Indian Land Tenure Foundation, the game was developed in collaboration with the Games for Entertainment and Learning Lab at Michigan State University thanks to support from the San Manuel Band of Mission Indians and the many Indigenous creatives who contributed design, art, music, and writing. Uniquely, When Rivers Were Trails is a sovereign game, meaning that it was directed and informed by Indigenous creatives who maintained the role of final decisions during development. Merging design research and close reading methods, this study sets out to describe the game’s design, development process in regards to the game writing, and the resulting themes which emerged as a result of engaging Indigenous writers in self-determined representations.
_eprint: https://doi.org/10.1080/13527258.2020.1746919
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le jeu vidéo comme vecteur d’expression du patrimoine culturel des Iñupiats d’Alaska - Hocine, Julien; Deslauriers, Patrick (Emulations - Revue de sciences sociales, 2019)
En 2014, une collaboration entre le studio Upper One Games et des conteurs et aînés iñupiats d’Alaska a mené au lancement du jeu vidéo Kisima Inŋitchuŋa (Never Alone). Ce jeu de plateforme invite à une immersion poétique dans un univers nordique guidée par une trame narrative inspirée d’une légende traditionnelle. Dans une perspective culturelle, les fonctions ludique et documentaire du jeu permettent d’acquérir des connaissances en lien avec les pratiques traditionnelles et la vision du monde des Iñupiats. Ainsi, l’étude exploratoire présentée dans cet article contribue à comprendre les caractéristiques du jeu (design, narration, mécaniques) et les stratégies relevant de sa conception. Les résultats invitent à reconsidérer des représentations dominantes du Grand Nord et soulignent en quoi le jeu vidéo se fait vecteur d’expression du patrimoine culturel, artistique et oral d’un peuple autochtone de l’Arctique.
Number: 30
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Exploring Collaborative Talk Among African-American Middle-School Girls in the Context of Game Design for Social Change - Thomas, Jakita O.; Rankin, Yolanda; Saunders, Quimeka (Journal of Computing Sciences in Colleges, 2019)
Computer Science education research establishes collaboration among students as a key component in learning, particularly its role in pair programming. Furthermore, research shows that girls, an underrepresented population in computing, benefit from collaborative learning environments, contributing to their persistence in CS. However, too few studies examine the role and benefits of collaborative learning, especially collaborative talk, among African-American girls in the context of complex tasks like designing video games for social change. In this exploratory study, we engage 4 dyads of African-American middle school girls in the task of designing a video game for social change, recording the dyads' conversations with their respective partners over an eight-week summer game design experience during the second year of what has now become a six-year study. Qualitative analysis of dyadic collaborative discussion reveals how collaborative talk evolves over time in African-American middle-school girls.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Pédagogie décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Mondes profanes: enseignement, fiction et histoire - Éthier, Marc-André 1969-; Lefrançois, David 1976-; Joly-Lavoie, Alexandre; Buysse, Alexandre. (Presses de l'Université Laval, 2018)
"Les bandes dessinées, chansons, films, jeux vidéos, musées, reconstitutions, romans, séries télévisées et voyages occupent de plus en plus de place dans la vie des élèves. Comment exploiter en classe ces biens, loisirs et services culturels d'histoire pour que les élèves posent de mieux en mieux certains actes mentaux que les historiennes et historiens doivent effectuer lorsqu'elles et ils adoptent leur pratique? Pour répondre à cette question, les auteures et auteurs de cet ouvrage explorent les usages scolaires possibles et souhaitables des produits qui ne sont pas associés à l'histoire savante et sur l'exploitation didactique de ce que la Loi québécoise sur les biens culturels désigne comme "?une oeuvre d'art, un bien historique, un monument ou un site historique ... une oeuvre cinématographique, audiovisuelle, photographique, radiophonique ou télévisuelle?". Les auteures et auteurs s'intéressent à des oeuvres qui ne sont pas créées pour l'école, mais qui peuvent néanmoins servir aux enseignantes et enseignants pour faire apprendre l'histoire aux élèves."–Résumé de l'éditeur.
Section: xvi, 515 pages ; 23 cm
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Interrogating Evil in Videogames about Violent Conflicts - Hammar, Emil Lundedal; Pötzsch, Holger (The Routledge International Handbook of Perpetrator Studies, 2020)
This contribution interrogates the figure of the perpetrator as it emerges in narrative videogames. First, we provide a brief outlook on some key characteristics of videogames, before we discuss how the specific affordances of this “new” medium offer unprecedented ways of approaching and dealing with perpetrators and perpetration. Finally, we offer concrete examples from three games to illustrate different possible configurations of the playerperpetrator nexus—Yager Development’s Spec Ops: The Line (2012), 11 Bit Studio’s This War of Mine (2015), and Hangar 13’s Mafia III (2016). In contrast to other media, games enable an active exploration of, and participation in, a variety of possible offenses. Rather than merely witnessing evil deeds, players are immersed in simulated environments that demand constant evaluations of complex settings and require decision-making under systemic limitations. This performative aspect of play makes games a unique medium for learning and teaching about the intricate logics and innate dynamics of perpetrations.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Étude des représentations; 4-Europe (lieu de production du savoir); _Nettoyé

Decolonising the Games Curriculum: Interventions in an Introductory Game Design Course - Geyser, Hanli (Open Library of Humanities, 2018)
Games face a crisis of diversity in both their content and in the industry itself. The inequalities that underlie these issues are heightened in the Global South. Addressing these issues will require a systemic decolonisation of games education in which future generations of industry professionals become critically engaged in their creative practice. Decolonisation requires the investigation and reconstruction of the ways knowledge is created and produced. To enable this, the curricula employed in teaching games requires close investigation and intervention. The difficulties of enabling access to knowledge when teaching games are exacerbated when seen in light of the need for decolonisation. Situated in a South African context, this article investigates the first-year core course ‘Key Concepts in Game Design’ offered at the University of the Witwatersrand in Johannesburg. It outlines the challenges games education faces in South Africa and takes stock of the state of the course and of the perceptions of students enrolled in it. It demonstrates that the course curriculum requires increased Africanisation and the establishment of common play practices. Finally, it highlights the importance of focusing on the development of critical game literacies as part of the decolonising project.
Number: 1
Keywords: 1-Jeux vidéo; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Afrique (lieu de production du savoir); 5-Autrice; _Nettoyé

Who Made Your Phone? Compassion and the Voice of the Oppressed in Phone Story and Burn the Boards - Navarro-Remesal, Víctor; Zapata, Beatriz Pérez (Open Library of Humanities, 2018)
Burn the Boards (Causa Creations, 2015) portrays the life of an Indian worker who recycles electronic waste in a precarious environment. Phone Story (Molleindustria, 2011) simulates the journey and process of production and consumption of mobile phones, from Congo and China to Pakistan. Whereas Phone Story is described as ‘an educational game’ that addresses the player directly as a consumer, Burn the Boards is a resource management puzzle that creates compassion through role playing. These games bring to the fore a hidden reality of the everyday that is ingrained in historical relationships and power dynamics, drawing attention to what Michael Rothberg has recognized as ‘exploitation in an age of globalized neo-liberal capitalism’ (2014: iv). This article explores how these games denounce the smartphone industry by using that same technology. For this purpose, we refer to Game Studies theory on procedural rhetoric; values and ethics; and the role of the player, combined with questions of (neo)colonization, globalization, and neoliberalism drawn from Postcolonial Studies. Our analysis shows the complicity of users and their confrontation with the extreme vulnerability of others, emphasizing how the coloniality of power works in our global consumer society. Thus we study the power relationships described and established by these games, the affective reactions which they seek to trigger, and their potential to transform players from passive observers into ethical players and consumers.
Number: 1
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Towards Diversity: Interventions in Curriculum and Pedagogy of an Introductory Game Design Course - Hanli, Geyser (DiGRA/FDG '16 - Abstract Proceedings of the First International Joint Conference of DiGRA and FDG, 2016)
Transformation and the decolonization of the curriculum, modes of teaching, and classroomare key concerns in South African Higher Education. In game design education this need is exacerbatedby the slow pace of diversification in both academia and the industry.This paper presents a close analysis of interventions undertaken into an introductory game design course to address the difficultiesof diversification across racial, genderand economic divides. The results of the interventions are assessed, and recommendations for future adjustments to the course in aid curricular decolonization is are made.
Place: Dundee, Scotland
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Autrice; _Nettoyé

Counter-Hegemonic Commemorative Play: Marginalized Pasts and the Politics of Memory in the Digital Game Assassin’s Creed: Freedom Cry - Hammar, Emil Lundedal (Rethinking History, 2015)
In this article, I argue that digital games hold the potential to influence processes of cultural memory related to past and contemporary forms of marginalization. By bringing cultural memory studies into dialogue with game studies, I account for the ways through which digital games and practices of play might influence historical discourses and memory politics pertaining to marginalized identities. In order to demonstrate this, I conduct an analysis of Assassin’s Creed: Freedom Cry, a digital game which includes representation of the eighteenth-century transatlantic slave trade and its racist systems. This analysis is then contrasted with statements by two critics, Evan Narcisse and Justin Clark, about how Freedom Cry highlights specific marginalized identities and represents the past through the game form. These statements, coupled with my game analysis, make the case for a concept that I term ‘counter-hegemonic commemorative play’. This makes visible a form of potentially cathartic power fantasy within a historical struggle, alongside emphasizing a form of designed recognition of marginalized identities within contemporary historical discourses and memory politics.
Number: 3
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Digital Arabs: Representation in Video Games - Šisler, Vít (European Journal of Cultural Studies, 2008)
This article presents the ways in which Muslims and Arabs are represented and represent themselves in video games. First, it analyses how various genres of European and American video games have constructed the Arab or Muslim Other. Within these games, it demonstrates how the diverse ethnic and religious identities of the Islamic world have been flattened out and reconstructed into a series of social typologies operating within a broader framework of terrorism and hostility. It then contrasts these broader trends in western digital representation with selected video games produced in the Arab world, whose authors have knowingly subverted and refashioned these stereotypes in two unique and quite different fashions. In conclusion, it considers the significance of western attempts to transcend simplified patterns of representation that have dominated the video game industry by offering what are known as 'serious' games.
Number: 2
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé